The Nature of Shocks in the Eurozone and Their Absorption Channels - Cinzia Alcidi; Mathias Dolls; Clemens Fuest; Carla Krolage; Florian Neumeier (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2017)
We investigate the degree of (a)symmetry of macroeconomic fluctuations within the euro area (EA). Our findings indicate, first, a high degree of co-movement of cyclical GDP across EA member states. However, the amplitudes of national business cycles appear to vary notably, meaning that booms and recessions differ with regard to their severity across EA member states. Second, the co-movement of cyclical unemployment is somewhat less pronounced than that of cyclical GDP and the sensitivity to common shocks is even more heterogeneous, suggesting that differences in labour market conditions play an important role with regard to the vulnerability to common shocks. Turning to potential stabilization mechanisms, we find that in general, the private sector has a huge potential to absorb asymmetric shocks. However, in international comparison, the shock-absorption capacity of the private sector in the EA is rather weak. Recent evidence suggests that promoting capital market integration may improve the private sector's shock absorption capacity.
Keywords: 330